Memória e ritmicidade circadiana em ratos adolescentes submetidos a um protocolo de dessincronização forçada- modelo T22 - Araújo , Kathlyn Kamoly Barbosa Cavalcanti (2017)
Temporal adaptation of the species to the environment is of fundamental importance to ensure survival. However, the rhythm of modern society increasingly induces the individual to desynchronization, both internal and external, as a result of abrupt phase changes such as night shift,r shift work or social Jet Lag. The same is observed in adolescent individuals who, in order to comply with curricular and extracurricular demands, adopt the habit of sleeping late and waking up early that leads to sleep deprivation and irregular hours of sleep and awakening. Thus, it is important to study the effects of chronic phase shifts on physiology and behavior of young mammals. In this work we attempt to characterize the effects of LD cycle of 22h , a model of internal forced desynchronization, on recognition memory of objects and space and the expression of circadian rhythmicity of adolescent rats. For this purpose, 44 male Wistar rats were used, divided into 2 groups: T24, n = 12 (LD 12:12 h) and T22, n = 30 (LD 11:11 h). The T22 group was subdivided into two groups that performed the tests, respectively: in the middle of coincidence nights between the environment and the biological night of each rat (n=16) and in the middle of non-coincidence nights (n=14). The tasks New Object Recognition and Associative Spatial Task were used. The locomotor activity of these animals was recorded continuously and totalized at 5 min intervals. Later it was analyzed by visual inspection of actograms and calculation of circadian periodicities using the program El Temps. We observed that rats under T22 presented two rhythms of motor activity, one synchronized to the environment, exhibiting the same period of the LD cycle, and other in free-running, expressing a period longer than 24h. Regarding the analyzed memory tasks, the animals under T22 presented a loss in their performance.Based on that, we conclude that the LD cycle of 22h promotes dissociation in the circadian rhythm of motor activity in adolescent rats, impairing their performance in the mnemonic tasks evaluated.